DESIGN AND ANALYSIS OF WORK OF TRANSPORT SYSTEMS WITH A FLEXIBLE HAULAGE ELEMENT - Martyntsiv, Myhaylo; Udovytskyy , Oleksandr (Forestry, Forest, Paper and Woodworking Industry, 2009)
The mathematical model of transport systems with a flexible element has been developed. Analytical dependences for determination of efforts in the branches of flexible haulage element taking into account the dynamic loadings have been obtained. The analysis of the obtained dependences, which allowed to substantiate optimum rates of movement and parameters of drive of such transport systems, has been carried out